ANALISIS ASPEK TEKNIS KAPAL PUKAT CINCIN (PURSE SEINE) DAN ALAT TANGKAP YANG DIGUNAKAN NELAYAN DI PERAIRAN TELUK BONE - Hawati Hawati; Angkasa Putra (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
The utilization of fish resources by fishermen in the waters of Bone Bay uses different fishing gear and patterns as well as different utilization and management policies. This can affect the sustainability of existing fish resources, one of which is in the Bone Regency area. This study aims to analyze the technical aspects of purse seine and fishing gear used by fishermen in the waters of Bone Bay, especially in Bone Regency. Furthermore, the technical aspects of the vessel and fishing gear as a result of the calculation are compared with the provisions stipulated in the PERMEN-KP Number 71 of 2016 to determine the zone of the fishing area. This research was conducted in Panyula Village, which is the fishing base area of purse seine fishermen and the waters of Teluk Bone, starting from November 2016 to March 2017. This research uses a combination of survey methods and case studies. The type of data used consists of primary data and secondary data. Based on the technical aspects of purse seine vessels, ring trawl fishing gear and FAD fishing tools, purse seine units should be operated on Fishing Route II and Fishing Route III in accordance with Minister of Marine Affairs and Fisheries Regulation Number 71 of 2016.